(untitled) (diségno, 2022)
The REAACH-ID (Representation for Enhancement and management through Augmented reality and Artificial intelligence: Cultural Heritage and Innovative Design) symposium is now in its third edition, which was held, again this year, in webinar mode, on the days (October 11-12, 2022) organized by the promoting committee composed by Andrea Giordano of the University of Padua, Michele Russo of Sapienza University of Rome and Roberta Spallone of the Politecnico di Torino. [read more]